Identification and Characterization of Constituents in Si-Wu-Tang by Liquid Chromatography Connected with Time of Flight Mass Spectrometry and Ion Trap Mass Spectrometry - Chen, Xiaopeng; Zhang, Lanlan; Zhou, Shuiping; Zhu, Yonghong; Liu, Changxiao (Asian Journal of Chemistry, 2013)
A combination of high performance liquid chromatography time of flight mass spectrometry (HPLC-TOF/MS) and high performance liquid chromatography coupled with diode array detection and electrospray ionization tandem mass spectrometry (HPLC-DAD-ESI-MS/MS) as a powerful method to profile and identify non-target components in traditional Chinese medicine (TCM) was developed. Si-Wu-Tang (SWT), a popular traditional Chinese medicine, was studied using the combinative method as for an application. Based on the mass spectra, UV spectra and retention time, 21 compounds were identified or tentatively characterized. This study represents the first detailed investigation of the components of Si-Wu-Tang with HPLC-TOF/MS technique. The identification and structural elucidation of the chemical constituents provided essential data for further quality control and pharmacological mechanism research of Si-Wu-Tang. With the introduction of the combinative HPLC-MS technique analytical system to traditional Chinese medicine, we expected that approach would be useful for the screening and characterization of non-target compounds in other famous traditional Chinese medicine.